Evidence-based position paper on the professional practice of Physical and Rehabilitation Medicine for persons with cerebral palsy. The European PRM position (UEMS PRM section) - Hornáček, Karol; Kujawa, Jolanta; Varela Donoso, Enrique; Dincer, Fitnat; Ilieva, Elena; Takáč, Peter; Petronic Markovic, Ivana; Votava, Jiří; Vetra, Anita; Nikolic, Dejan; Christodoulou, Nicolas; Zampolini, Mauro; et al. (European Journal of Physical and Rehabilitation Medicine, 2021)
Cerebral palsy (CP) is a group of the most common developmental disorders affecting movement and posture of the body, causing activity limitations and participation restrictions. The motor disorders of persons with CP are often accompanied by disturbances of sensation, cognition, communication and perception. The symptoms of CP are very diverse and persons with CP are usually presented with a mixed type of symptoms. The non-progressive disturbances can be attributed to disorders that were developed during pregnancy, birth and/or infant stage. The aim of this study was to improve physicians' professional practice of Physical and Rehabilitation Medicine for persons with cerebral palsy in order to improve their functionality, social and community integration, and to reduce activity limitations and/or participation restrictions. A systematic review of the literature including an 18-year period and consensus procedure by means of a Delphi process was performed and involved the delegates of all European countries represented in the Union of European Medical Specialists Physical and Rehabilitation Medicine (UEMS PRM) Section. As the result of a Consensus Delphi procedure, 74 recommendations are presented together with the systematic literature review. The PRM physician's role for persons with cerebral palsy is to lead and coordinate the multiprofessional team, working in an interdisciplinary way. They should propose and manage the complex but individual PRM program developed in conjunction with other health professionals, medical specialists and importantly in agreement with the patient, their family and care giver. This should be, according to the specific medical diagnosis to improve patients' health, functioning, social and education status, considering all impairments, comorbidities and complications, activity limitations and participation restrictions. This evidence-based position paper is representing the official position of The European Union through the UEMS PRM Section and designates the professional role of PRM physicians in persons with cerebral palsy.
Keywords: odborná praxe; lidé; Professional Practice; Europe; rehabilitační lékařství; Evropa; mozková obrna; Cerebral Palsy; Physical and Rehabilitation Medicine; Humans